P1254CARDIAC TISSUE CHARACTERISATION AND AUTONOMIC FUNCTION IN PATIENTS WITH CHRONIC KIDNEY DISEASE AND ON HAEMODIALYSIS: A PILOT STUDY. (6th June 2020) - Cokljat, Mia; Bunce, Nicholas; He, Taigang; Banerjee, Debasish
Abstract: Background and Aims: Sudden cardiac death rates are higher in patients with CKD and on haemodialysis. Hypotheses include the presence of diffuse myocardial fibrosis secondary to fluid and toxin overload. Native T1, T2 and T2* mapping through cardiac magnetic resonance (CMR) is emerging as a novel technique to quantify myocardial fibrosis. This pilot study aimed to quantify cardiac morphological change using CMR native T1, T2 and T2* mapping and correlate with autonomic provocation testing, in CKD 3b-5 and haemodialysis patients. Method: Patients with stable CKD 3b and higher, and patients on haemodialysis (CKD-haemodilaysis) underwent a non-contrast CMR, which included native T1, T2, T2* mapping. Autonomic provocation testing was performed using a dipolar ECG lead, followed by 14-days of recording. Results were compared between patient groups, and T1, T2, T2* maps compared to healthy controls using the student t test and Kruskal-Wallis tests. Results: Nine CKD, eight haemodialysis and seven control patients were recruited (Table 1). Of the late-stage CKD patients, three were stage 3b, four were stage 4 and two were stage 5. There were no significant differences between the two patient groups in baseline characteristics (Table 1). There were no significant differences between CKD and CKD-haemodialysis patients in left ventricular end-diastolic volume index, left ventricular end-systolic volume index, right ventricular end-diastolic volume index, right ventricular end-systolic volume index, ejection fraction, and left ventricular mass index (71.1±15.2 vs. 80.51 ±21.9 ml/m 2, p=0.316; 24.4±7.09 vs. 34.4±19.4 ml/m 2, p=0.171; 67.11 ± 14.9 vs. 75.5±23.4 ml/m 2, p=0.386; 22.2±4.87 vs. 23.9±9.93 ml/m 2, p=0.663 ; 65.8±6.34 vs. 59.5±12.4 %, p=0.200; 48.4±8.60 vs. 50.5±11.0 g/m 2, p=0.673 ). T1 and T2 were significantly increased in CKD and CKD-haemodialysis patients compared to healthy controls (1259±57.7 vs. 1204±22.3 ms, p=0.038 and 49.1±4.74 vs. 42.0±2.79 ms, p=0.034 ). There was no difference in T2* star ( 32.8±7.59 vs. 28.8±3.77, p=0.291). There was no significant difference in native T1, T2 and T2* times between CKD and CKD-haemodialysis patients (1247±66.7 vs. 1273±45.7, p=0.361; 49.1±5.22 vs. 49.0±4.49, p=0.960; 34.1±7.57 vs. 31.3±7.81, p=0.769) . Mean percentage change of HR in CKD patients from lying to sitting to standing was 4.51%±6.66 and 11.5%±11.8 respectively. Mean percentage change of HR in CKD-haemodialysis from lying to sitting to standing was 2.15%±6.30 and 6.0%±4.45 respectively. There were no significant differences in postural HR variability between CKD and CKD-haemodialysis patients ( p=0.478 and p=0.237). Conclusion: In late stage CKD, cardiac volumes, mass, ejection fraction and native T1, T2 and T2* are comparable to those of patients on long-term haemodialysis. However native T1 and T2 times are significantly elevated in later stage CKD and haemodialysis, compared to healthy controls. Heart rate changes over postural provocation are comparable between CKD and CKD-haemodialysis patients, although autonomic response is reduced compared to previously published data in healthy controls. Processes that drive myocardial fibrosis may start earlier in CKD pathogenesis.